Effectiveness of Camellia Sinensis L Extract in Inhibiting the Growth of Staphylococcus aureus - Asmah, Nur; Ilmianti, Ilmianti; Abdi, Muhammad Jayadi; Irawati, Erna; Nursaid, Herawati (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Gingivitis and periodontitis are the two most common periodontal conditions. Staphylococcus aureus was reported as a trigger. Compounds active from the green ( Camellia Sinensis L) have been reported to be beneficial as antibacterial. Objective: know the effectiveness of extract tea leaves green 8%, 10%, and 12% in inhibiting bacterial growth of Staphylococcus aureus. Method: The study was conducted in a way that involved 25 power resistors. S. aureus was assessed with a diffusion disc technique with a post-test type-only control design. As well as test statistics Kruskal-Wallis. Results: Based on The results of the Kruskal-Wallis test showed a p-value of 0.0000.05. So, there was a significant difference between the 8%, 10%, and 12% extract treatments and the control group. Conclusion: Extracting leaves with a green concentration of 12% effectively hinders bacteria Staphylococcus aureus.